1979
DOI: 10.1677/joe.0.0820053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Testicular Function on the Pituitary–thyroid System in Male Rats

Abstract: Old male rats of 22\p=n-\24 months and young ones of 3\ p=n-\ 5 months were studied to find the effects of ageing, of orchidectomy and of orchidectomy and treatment with testosterone propionate (TP) on the basal serum concentrations of thyrotrophin (TSH) and on the total and free concentrations of tri-iodothyronine (T3) and thyroxine (T4) in the serum. The changes in TSH after treatment with thyrotrophin releasing hormone (TRH) were also observed. Intact old rats had significantly (P < 0\m=.\001) lower basal T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0

Year Published

1983
1983
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 9 publications
5
10
0
Order By: Relevance
“…It is well recognized that castration decreases levels of TSH in peripheral blood of male rats [27], The castrationinduced reduction of TSH levels is completely reversed by testosterone substitution [27] (present study). Pekary et al [28] reported that castration increased TRH (as deter mined by RIA and HPLC analysis) in the PP, while reduc ing in vitro TRH release from the hypothalamus.…”
Section: Discussionsupporting
confidence: 59%
“…It is well recognized that castration decreases levels of TSH in peripheral blood of male rats [27], The castrationinduced reduction of TSH levels is completely reversed by testosterone substitution [27] (present study). Pekary et al [28] reported that castration increased TRH (as deter mined by RIA and HPLC analysis) in the PP, while reduc ing in vitro TRH release from the hypothalamus.…”
Section: Discussionsupporting
confidence: 59%
“…Age-related decreases in hypothalamic tuberoinfundibular dopamingergic neuronal activity contribute to in creased basal and stimulated PRL levels in old rats [41,42], Because testosterone inhibits these neurons during stress [43], and circulating levels of testosterone decrease with age [44], alterations in dopaminergic and androgenic inputs may have contributed to the exaggerated PRL response to Immo in old rats in this study. Failure of the ultrashort loop negative feedback mechanism of PRL secretion in old rats might also be a contributing factor [45].The increased levels of immunoreactive PRL in old rats during Immo do not necessarily correspond to in creased biological effects, as the biological activity of PRL declines with age [46], In the current study, the levels of immunoreactive GH were similar at baseline and were significantly inhibited by Immo in both young and old rats.…”
Section: Discussionmentioning
confidence: 63%
“…Intact male rodents exhibit wide individual differences in androgen production as a function of such factors as age (Chen and Walfish, 1979;Gray, 19781, exposure to a female (Taylor et al, 1983a), and prior sexual experience (Taylor et al, 1983b). The present findings suggest that different suprathreshold levels of TP can provoke different structural changes in the penes of male rats.…”
Section: Discussionmentioning
confidence: 99%